2014
DOI: 10.7567/apex.7.063005
|View full text |Cite
|
Sign up to set email alerts
|

Bias field angle dependence of the self-oscillation of spin torque oscillators having a perpendicularly magnetized free layer and in-plane magnetized reference layer

Abstract: We report on the oscillation behavior of spin torque oscillators having a perpendicularly magnetized free layer and in-plane magnetized reference layer as a function of bias field angle. The measurement results show that both emission power and oscillation frequency are strongly dependent on the bias field angle. When the bias field was tilted by only a few degrees away from the axis normal to the film toward either parallel or antiparallel configuration, the power increased by about 1.5 times or decreased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
(27 reference statements)
1
10
0
1
Order By: Relevance
“…These behaviors are exactly what were predicted in the theory described in Ref. 39. Figure 4(a) shows the power spectral density with the increase of current at zero applied magnetic field for β = −0.1.…”
Section: Resultssupporting
confidence: 68%
“…These behaviors are exactly what were predicted in the theory described in Ref. 39. Figure 4(a) shows the power spectral density with the increase of current at zero applied magnetic field for β = −0.1.…”
Section: Resultssupporting
confidence: 68%
“…In other geometries, the experimental studies have shown that the oscillation properties such as the threshold current to excite the self-oscillation strongly depend on the field direction [6,10]. On the other hand, the role of the magnetic field on the self-oscillation properties in this geometry has not been fully understood yet.…”
Section: Introductionmentioning
confidence: 97%
“…The spin torque provides a rich variety of magnetization dynamics such as switching or self-oscillation [4][5][6][7][8][9][10]. In particular, a spin-torque oscillator consisting of an in-plane magnetized free layer and a perpendicularly magnetized pinned layer has been an attractive research subject in the field of magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Spin torque oscillators (STOs), which generate a continuous microwave signal by first exciting spin precession through spin transfer torque (STT) 1 2 and next converting it to an electrical signal through magneto-resistance (MR) effect, possess many attractive features for the above mentioned applications, such as nano-scale dimension due to self-oscillation without resonance circuits, low power operation, wide frequency tunability and compatibility with semiconductor fabrication processes. These make STO a promising candidate for the next generation microwave signal sources, and therefore since its initial experimental demonstrations 3 4 5 6 , extensive research efforts have been devoted to improve the STO’s basic performances such as emission power and quality factor (Q factor) 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 . Deac et al demonstrated a large emission power (>0.1 μW) in MTJ-based STO 13 due to the giant MR ratio of MgO-based magnetic tunnel junction (MTJ) 30 31 .…”
mentioning
confidence: 99%